Intrapopulation variation in lower limb trabecular architecture. Issue 1 (11th April 2020) - Mulder, Bram; Stock, Jay T.; Saers, Jaap P. P.; Inskip, Sarah A.; Cessford, Craig; Robb, John E.
Abstract: Objectives: Trabecular structure is frequently used to differentiate between highly divergent mechanical environments. Less is known regarding the response of the structural properties to more subtle behavioral differences, as the range of intrapopulation variation in trabecular architecture is rarely studied. Examining the extent to which lower limb trabecular architecture varies when inferred mobility levels and environment are consistent between groups within a relatively homogenous population may aid in the contextualization of interpopulation differences, improve detectability of sexual dimorphism in trabecular structure, and improve our understanding of trabecular bone functional adaptation. Materials and methods: The study sample was composed of adult individuals from three high/late medieval cemeteries from Cambridge (10th–16th c.), a hospital ( n = 57), a parish cemetery ( n = 44) and a friary ( n = 14). Trabecular architecture was quantified in the epiphyses of the femur and tibia, using high resolution computed tomography. Results: The parish individuals had the lowest bone volume fraction and trabecular thickness in most regions. Multiple sex differences were observed, but the patterns were not consistent across volumes of interest. Discussion: Differences between the three groups highlight the great variability of trabecular bone architecture, even within a single sedentary population. This indicates that trabecular bone may be used in interpreting subtle behavioral differences, and suggests that multiple archaeological sites need to be studied to characterize structural variation on a population level. Variation in sex and group differences across anatomical locations further demonstrates the site‐specificity in trabecular bone functional adaptation, which might explain why little consistent sexual dimorphism has been reported previously.